Ziziphus lotus (L.) Lam. as a Source of Health Promoting Products: Metabolomic Profile, Antioxidant and Tyrosinase Inhibitory Activities. Issue 6 (17th May 2022) - Cacciola, Anna; D'Angelo, Valeria; Raimondo, Francesco M.; Germanò, Maria Paola; Braca, Alessandra; De Leo, Marinella
Abstract: The methanolic extract of the stem bark of a wild species of jujube, Ziziphus lotus (L.) Lam., growing in Sicily, was chemically and biologically investigated. The chemical profile was defined by UHPLC‐HR‐ESI‐Orbitrap/MS analysis whereas antioxidant and tyrosinase inhibitory activities were investigated by in vitro assays. The extract showed a high total phenolic and flavonoid content (TPC=271.65 GAE/g and TFC=188.11 RE/g extract). Metabolomic analysis revealed a rich phytocomplex characterized by phenols, cyclopeptide alkaloids, and triterpenoid saponins, some of which here detected for the first time. The mushroom tyrosinase inhibition assay displayed that the methanolic extract efficiently inhibits the monophenolase and diphenolase activity. Furthermore, the extract showed a strong ability to scavenge DPPH, a good Fe 3+ reducing antioxidant power, in addition to a Fe 2+ chelating activity. Taken together, these results suggest possible novel applications of wild jujube stem bark as a source of potential skin‐care agents with several uses in pharmaceutical and cosmetic industries. Abstract :